The Job Stress, Work Environment, and Motivation Predicted the Staff Loyalty - Adyllon, Devand; Nugroho, Natsir; Liana, Duta (Alta Dharma Publisher, 2025)
Background: The intricate relationship between job stress, work environment, motivation, and staff loyalty has been a focal point of organizational studies for decades. Objective: This research aims to determine the relationship between work stress, work environment, and work motivation on staff loyalty. Method: This research is a quantitative study with a cross sectional approach involving 192 respondents. The research sample was taken using the Simple Random Sampling technique. Data was taken using a questionnaire. Data were analyzed using the Smart PLS version 3 program. Result: This research shows that there is a relationship between work stress and staff loyalty; work stress with work motivation; work environment with staff loyalty; work environment with work motivation; work environment with work stress; and work motivation with staff loyalty with a P value <0.05. Conclusion: in conclusion explained that job stress, work environtment, and motivation was successfully predicting the staff loyalty in the hospital. Recommendation: The hospital staff need to consider those factors to influence the staff loyalty at hospital. Further research needs to conduct the mixed method study to explore the factors associated with staff loyalty in qualitatively